A case report of urethral stricture of a 3 months old female child (Bangladesh Journal of Medical Science, 2023)
Background: Urethral stricture is a narrowing of the urethra which can either be congenital or acquired. In most cases, it is an acquired disorder. Congenital stricture is less common and even less commonly found in paediatric population.Case presentation: A 4-Month-old baby attended outpatient department with complaint of high fever and excessive crying that was more pronounced before and during urination along with whitish discharge mixed with urine. Urine R/M/E detected plenty pus cell. Left ureter appears grossly dilated, tortuous in USG. Constriction is noted in the distal part of urethra with proximal dilatation with bilateral vesico-ureteric reflux.Conclusion: As, no other cause i.e., iatrogenic, traumatic, inflammatory, post-infectious, was found out, there remain only one possibility for this baby having urethral stricture which is idiopathic or congenital cause.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 239-241